At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Sure, let's break down and solve this problem step-by-step.
Let's denote the smaller number by [tex]\( x \)[/tex] and the larger number by [tex]\( y \)[/tex].
### Step 1: Establish the equations from the given conditions
Condition 1: The larger number is 2 more than 3 times the smaller number.
This can be expressed as:
[tex]\[ y = 3x + 2 \][/tex]
Condition 2: If 3 is added to the smaller number and 1 to the larger number, they will be in the ratio 3:7.
This can be expressed as:
[tex]\[ \frac{x + 3}{y + 1} = \frac{3}{7} \][/tex]
### Step 2: Simplify the second equation
Cross-multiply to get rid of the fraction:
[tex]\[ 7(x + 3) = 3(y + 1) \][/tex]
Distribute and simplify:
[tex]\[ 7x + 21 = 3y + 3 \][/tex]
[tex]\[ 7x + 21 - 3 = 3y \][/tex]
[tex]\[ 7x + 18 = 3y \][/tex]
### Step 3: Substitute the first equation into the simplified second equation
From the first equation, we know [tex]\( y = 3x + 2 \)[/tex]. Substitute [tex]\( y \)[/tex] in the simplified second equation:
[tex]\[ 7x + 18 = 3(3x + 2) \][/tex]
[tex]\[ 7x + 18 = 9x + 6 \][/tex]
### Step 4: Solve for [tex]\( x \)[/tex]
Rearrange the equation to isolate [tex]\( x \)[/tex]:
[tex]\[ 7x + 18 - 9x = 6 \][/tex]
[tex]\[ -2x + 18 = 6 \][/tex]
[tex]\[ -2x = 6 - 18 \][/tex]
[tex]\[ -2x = -12 \][/tex]
[tex]\[ x = 6 \][/tex]
So, the smaller number [tex]\( x \)[/tex] is 6.
### Step 5: Find [tex]\( y \)[/tex] using the value of [tex]\( x \)[/tex]
Substitute [tex]\( x = 6 \)[/tex] into the first equation [tex]\( y = 3x + 2 \)[/tex]:
[tex]\[ y = 3(6) + 2 \][/tex]
[tex]\[ y = 18 + 2 \][/tex]
[tex]\[ y = 20 \][/tex]
So, the larger number [tex]\( y \)[/tex] is 20.
### Conclusion
The two numbers are:
- The smaller number is 6.
- The larger number is 20.
Let's denote the smaller number by [tex]\( x \)[/tex] and the larger number by [tex]\( y \)[/tex].
### Step 1: Establish the equations from the given conditions
Condition 1: The larger number is 2 more than 3 times the smaller number.
This can be expressed as:
[tex]\[ y = 3x + 2 \][/tex]
Condition 2: If 3 is added to the smaller number and 1 to the larger number, they will be in the ratio 3:7.
This can be expressed as:
[tex]\[ \frac{x + 3}{y + 1} = \frac{3}{7} \][/tex]
### Step 2: Simplify the second equation
Cross-multiply to get rid of the fraction:
[tex]\[ 7(x + 3) = 3(y + 1) \][/tex]
Distribute and simplify:
[tex]\[ 7x + 21 = 3y + 3 \][/tex]
[tex]\[ 7x + 21 - 3 = 3y \][/tex]
[tex]\[ 7x + 18 = 3y \][/tex]
### Step 3: Substitute the first equation into the simplified second equation
From the first equation, we know [tex]\( y = 3x + 2 \)[/tex]. Substitute [tex]\( y \)[/tex] in the simplified second equation:
[tex]\[ 7x + 18 = 3(3x + 2) \][/tex]
[tex]\[ 7x + 18 = 9x + 6 \][/tex]
### Step 4: Solve for [tex]\( x \)[/tex]
Rearrange the equation to isolate [tex]\( x \)[/tex]:
[tex]\[ 7x + 18 - 9x = 6 \][/tex]
[tex]\[ -2x + 18 = 6 \][/tex]
[tex]\[ -2x = 6 - 18 \][/tex]
[tex]\[ -2x = -12 \][/tex]
[tex]\[ x = 6 \][/tex]
So, the smaller number [tex]\( x \)[/tex] is 6.
### Step 5: Find [tex]\( y \)[/tex] using the value of [tex]\( x \)[/tex]
Substitute [tex]\( x = 6 \)[/tex] into the first equation [tex]\( y = 3x + 2 \)[/tex]:
[tex]\[ y = 3(6) + 2 \][/tex]
[tex]\[ y = 18 + 2 \][/tex]
[tex]\[ y = 20 \][/tex]
So, the larger number [tex]\( y \)[/tex] is 20.
### Conclusion
The two numbers are:
- The smaller number is 6.
- The larger number is 20.
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.